2022
DOI: 10.12688/wellcomeopenres.17636.2
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of transplacental transfer of respiratory syncytial virus (RSV) specific antibodies among pregnant women in Kenya

Abstract: Background: Maternal immunisation to boost respiratory syncytial virus (RSV) antibodies in pregnant women, is a strategy being considered to enhance infant protection from severe RSV associated disease. However, little is known about the efficiency of transplacental transfer of RSV-specific antibodies in a setting with a high burden of malaria and HIV, to guide the implementation of such a vaccination program. Methods: Using a plaque reduction neutralization assay, we screened 400 pairs of cord and maternal se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…A more recent study assessing RSV CMR among 75 Alaska Native mother-infant pairs found that infants with CMR < 1.0 were more likely to be lower birth weight or preterm than infants with CMR > 1.0 [54] . Similar findings were noted in a recent study of pregnant women in Kenya [55] . In contrast, among a prospective cohort of 310 infants in rural Nepal, they did not find a statistically significant difference in RSV antibody transfer by GA in weeks, or between term and pre-term infants [27] .…”
Section: Potential Inhibitors Of Transplacental Transfer Of Maternal ...supporting
confidence: 91%
See 1 more Smart Citation
“…A more recent study assessing RSV CMR among 75 Alaska Native mother-infant pairs found that infants with CMR < 1.0 were more likely to be lower birth weight or preterm than infants with CMR > 1.0 [54] . Similar findings were noted in a recent study of pregnant women in Kenya [55] . In contrast, among a prospective cohort of 310 infants in rural Nepal, they did not find a statistically significant difference in RSV antibody transfer by GA in weeks, or between term and pre-term infants [27] .…”
Section: Potential Inhibitors Of Transplacental Transfer Of Maternal ...supporting
confidence: 91%
“…HIV : Numerous studies in LMICs, including Bangladesh [71] , Botswana [72] , Brazil [58] , [73] , Cameroon [74] , Kenya [48] , [55] , [60] , [61] , [75] , Malawi [59] , Mozambique [70] , Nigeria [76] , and South Africa [77] , [78] , [79] , [80] , [81] have evaluated differences in maternal antibody levels and CMRs for various pathogens in cohorts of women with and without HIV. While there is some variation in findings across study settings, most show HIV-positive pregnant women have lower specific antibody titers during pregnancy compared to their HIV-negative peers and demonstrate impaired transplacental transfer, resulting in lower mean CMRs, lower mean antibody concentrations, and/or higher proportion of infants born with antibody levels below protective thresholds among their infants compared to those born to HIV-negative women.…”
Section: Potential Inhibitors Of Transplacental Transfer Of Maternal ...mentioning
confidence: 99%
“… 20 In a recent study on two cohorts of pregnant women from two cities in Kenya, it was shown that the efficiency of maternal transfer of antibodies, measured as cord to maternal titer ratio (CMTR) was reduced when the number of pregnancies was >6, indicating that some mechanisms of antibody transfer become less efficient as the number of viable pregnancies increased. 36 Although our results reflect only two pregnancies in cotton rats, our data might reflect a gradual reduction in the efficiency of transfer of antibodies from dams to pups that should be considered for further mechanistic studies, especially due to the impact that this can have on efficacy of human vaccinees.…”
Section: Discussionmentioning
confidence: 75%
“…In Siaya County, additional data were collected from two hospitals, Bondo County Hospital and Siaya County Referral Hospital, leveraging on existing platform for surveillance of influenza disease among pregnant women. This surveillance is also led by KEMRI-CGHR in collaboration with US CDC 17 , 18 .…”
Section: Methodsmentioning
confidence: 99%